Voltammetric Detection of Irbesartan by Molecularly Imprinted Polymer (MIP)-Modified Screen-Printed Electrodes - Camilla Zanoni; Riccardo Rovida; Lisa Rita Magnaghi; Raffaela Biesuz; Giancarla Alberti (Chemosensors, 2022)
Irbesartan is a drug used to treat hypertension and high blood pressure. Recent studies associated sartans with several forms of cancer, making removing this class of substances from the environment a high priority. The EU has categorized drugs as emerging pollutants, and they can be more potent than other substances because they were designed to operate at low concentrations. Thus, effective and sensitive methods of determining Irbesartan selectively and accurately in environmental samples are necessary. MIPs have already been used to remove pollutants from complex matrixes, so they were also chosen for this work. In particular, a polyacrylate-based MIP was used to functionalize the graphite working electrode of screen-printed cells (SPCs), aiming to develop a voltammetric method for Irbesartan sensing. The MIP composition and the experimental conditions for the electrochemical determination were optimized through a Design of Experiments (DoE) approach. The whole analysis was replicated with different SPCs obtaining similar results, which highlight the good reproducibility potential. MIP-based electrodes were also applied to determine Irbesartan in fortified tap water samples, obtaining high recovery percentages. Given the good results, the electrochemical method based on MIP-modified screen-printed electrodes is promising for quantifying Irbesartan at a trace level.